EFEKTIVITAS METODE PROBING PROMPTING LEARNING DALAM PEMBELAJARAN MENULIS ARGUMENTASI - Fajar Gumelar (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
One type of writing that must be mastered by students is an argument. Facts on the ground indicate that, learning to write arguments still less effective. This is due to the learning methods used by teachers less varied and monotonous. Therefore, teachers should select appropriate learning methods. One is the probing prompting method of learning. The purpose of this study to determine whether there is a significant difference between the ability of high school students of class XI in writing the argument before and after the learning using probing prompting method of learning. The method used is a quasi experimental model to study the design of the control group pre-test-post-test. This study tested the hypothesis that there are significant differences between the ability to write an argument with the learning method probing prompting learning with other learning methods are applied in teaching writing argumentation. After analyzing the research data, the result ttable tcount ttable or 2.03 2.59 2.03. That is, there are significant differences between students' ability in writing argumentation before and after using the learning methods of probing prompting learning.Keywords: writing, argumentation, the method, probing prompting learning.